KESALAHAN KALIMAT BAHASA INDONESIA DALAM TEKS ANEKDOT KARYA SISWA KELAS X SMAN 1 GUNUNG TALANG KABUPATEN SOLOK - Septria, Fauzie; Agustina, Agustina; Manaf, Ngusman Abdul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This research is motivated by the ability of students of class X SMAN 1 Gunung Talang in Solok regency writing anecdotes text low. One of the causes of the low quality of writing anecdotes it is the number of syntax errors. This study aimed to describe the syntax errors in the text anecdotal review of aspects, (1) the structure of syntactic function, (2) the adequacy element of the sentence, (3), the waste element of the sentence, (4) choice of words, (5) punctuation and spelling. The research is a qualitative descriptive method. This research data is wrong Indonesian words contained in the text of anecdotes works graders X SMAN 1 Gunung Talang in Solok regency. Data were analyzed based on the theory of error analysis and syntactic theory Indonesian. The research showed the following data: syntax errors in terms of structure function syntax, sentence errors in terms of the adequacy of the sentence elements, sentence errors in terms of wastefulness elements of sentences, syntax errors in terms of word choice and syntax errors in terms of punctuation and spelling.Â Kata kunci: kesalahan kalimat, teks anekdot